2011
DOI: 10.1080/03736245.2011.610131
|View full text |Cite
|
Sign up to set email alerts
|

A new theory for an age-old problem: ecological modernisation and the production of nuclear energy in South Africa

Abstract: South Africa has historically enjoyed an ability to generate energy cheaply through the use of abundant coal reserves, which has been a key component in the promotion of economic growth. This paper assesses whether it is possible to reconcile economic goals and environmental protection within the nuclear energy sector, whilst meeting the needs of society. Simultaneous economic growth and environmental protection through the use of more efficient technologies have been achieved in the industrialised North, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Many South African scholars, unsatisfied with the relevance of EM and EJ in South Africa, have sought to reshape these discourses through productive engagement: Dixon and Ramutsindela (2006) argue for an expanded definition of EJ to include risk and relocation; Oelofse et al. (2006) explore shifts in the practice of EM (which they similarly identify as the dominant) in South Africa towards more participatory practices; and Long and Patel (2011) similarly argue for a synthesis of EM and EJ to respond to the nuclear energy debate. It is possible that these repeated efforts to combine two existing international discourses suggest their salience and relevance to South Africa.…”
Section: Environmental Research In South Africa: What We Seementioning
confidence: 99%
“…Many South African scholars, unsatisfied with the relevance of EM and EJ in South Africa, have sought to reshape these discourses through productive engagement: Dixon and Ramutsindela (2006) argue for an expanded definition of EJ to include risk and relocation; Oelofse et al. (2006) explore shifts in the practice of EM (which they similarly identify as the dominant) in South Africa towards more participatory practices; and Long and Patel (2011) similarly argue for a synthesis of EM and EJ to respond to the nuclear energy debate. It is possible that these repeated efforts to combine two existing international discourses suggest their salience and relevance to South Africa.…”
Section: Environmental Research In South Africa: What We Seementioning
confidence: 99%
“…Moreover a 'strong' EM approach may be more critical of the intergenerational consequences of nuclear waste. This discourse can be related to arguments to include environmental justice as a consideration [69].…”
Section: Weak Ecological Modernisationmentioning
confidence: 99%
“…In the literature reviewed above, EJ and EM are typically portrayed as opposing discourses (cf Bond, 2000;Long and Patel, 2010;Oelofse et al, 2006). Simply put, it has been suggested that EM focuses on the environment and economy, while EJ focuses on the social and environmental.…”
Section: Interactions Between Environmental Justice and Ecological Momentioning
confidence: 99%